Reviews of new publications - Holmes, Derek A; van Balen, Bas (KUKILA, 1995)
MacKinnon, J. & K. Phillipps. 1993. A field guide to the birds of Borneo, Sumatra, Java and Ball. Oxford University Press Madge, S. & H. Brown (date not given). Crows & Jays. Helm/A& C Black, London Clement, P., A. Harris & J. Davis (1993). Finches & Sparrows. Helm, London Smith, S.W. (1993-1994). Bird recordings from the Moluccas, Lesser Sundas, Sulawesi and Java, Ball & Sumatra Gibbs, D. Indonesia 1990. Pilai Poonswad & Alan C. Kemp (eds.). 1993. Manual to the conservation of Asian Hornbills. Hornbill Project, Dept. of Microbiology, Faculty of Science, Mahidol University, Bangkok, Thailand Bock, Walter J. (1994). History and nomenclature of avian family-group names. Bull. Am. Mus. Nat. Hist. No. 222.